H2O2/Ca2+/Zn2+ Complex Can Be Considered a "Collaborative Sensor" of the Mitochondrial Capacity? - Ester Sara Di Filippo; Franco Checcaglini; Giorgio Fanò-Illic; Stefania Fulle (MDPI AG, 2022)
In order to maintain a state of well-being, the cell needs a functional control center that allows it to respond to changes in the internal and surrounding environments and, at the same time, carry out the necessary metabolic functions. In this review, we identify the mitochondrion as such an "agora", in which three main messengers are able to collaborate and activate adaptive response mechanisms. Such response generators, which we have identified as H2O2, Ca2+, and Zn2+, are capable of "reading" the environment and talking to each other in cooperation with the mitochondrion. In this manner, these messengers exchange information and generate a holistic response of the whole cell, dependent on its functional state. In this review, to corroborate this claim, we analyzed the role these actors, which in the review we call "sensors", play in the regulation of skeletal muscle contractile capacities chosen as a model of crosstalk between Ca2+, Zn2+, and H2O2.